Carolina's Caribbean Origins: A Review of Hubs of Empire - Robert Goddard (Southern Spaces, 2015)
Robert Goddard reviews Matthew Mulcahy's Hubs of Empire: The Southeastern Lowcountry and British Caribbean (Baltimore: Johns Hopkins University Press, 2014).